Literature Review of Quality Control Circle (QCC) and Implementation Recommendation to the Defense Industries - Baisalim, Muhammad Fikri; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
The purpose of this article is to explore the benefits of implementing the Quality Control Circle (QCC) in various industries and provide suggestions for application to the defense industry. The method of writing this article is a literature review, namely reviewing by collecting, understanding, analyzing and then concluding as many as 25 international journal articles on Quality Control Circle (QCC) published from 2015 to 2021 regarding the application of the Quality Control Circle (QCC) method in various industrial sectors and the defense industry. The analysis used used 25 content analysis of journal articles. The results of the literature review analysis state that the implementation of a quality control circle (QCC) can have benefits for companies and employees such as increasing quality awareness at all levels of the organization, fostering employee self-longing towards the company, increasing team work between employees and between departments (departments), increasing efficiency. process, increasing employee motivation, increasing customer satisfaction, QCC as a promotional tool from the company, establishing cooperation with other companies through QCC, QCC as a tool for exchanging information with other companies, channeling their thinking ability through discussion, brainstorming, improving their work ability through group collaboration, improve cooperation skills, improve communication skills, always be introspective, think patterns become more critical, increase creativity. quality control circle (QCC) is recommended to be applied in the defense industry. Quality Control Circle (QCC) is recommended to be applied in the defense industry